Model Dakwah dan Perubahan Sosial Masyarakat Desa Ciomas Ciamis - Ahmadi - - (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2021)
ABSTRACTThis study aims to determine the model of da'wah and social change of Ciomas Village, Ciamis Regency in 2012-2021. The research method uses a qualitative with case study approach. This study uses the theory of da'wah of Amrullah Ahmad (1983) and the theory of social change system Piotr Sztompka (2004). The results show that the da'wah model of Ciomas Village, Ciamis Regency, has three forms of models: Tarbiyatul Diniyah, Tazkiyatul Nafsiyah, and Tabliqul Ilmi wal Amaliyah. The social changes that occurred include: First, religious traditions have the Sunnah Fasting Tradition, the circumcision tradition, wedding party, babarit tradition, Cukuran tradition, and Manaqiban tradition. Second, the change in social status in the Cisirri Block of Ciceuri Hamlet has changed in increasing education and increased opportunities to seek income and other businesses. Third, socio-economic changes in the Cisirri Block of Ciceuri Hamlet increased welfare in terms of economy and infrastructure. The drivers of social change are due to many factors, while the barriers to social change are due to the late development of science and habits. The impact of this research is expected to be a reference model of da'wah for other communities and a contribution to the development of da'wah science.Keywords : Da'wah Model, Social Change